Documents on the Polish-Crimean Tatar Diplomatic Relations. Part 2 - Sebastian Cwiklinski (Крымское историческое обозрение, 2019)
The article offers a new transcription of the Crimean Tatar documents on the Polish-Crimean Tatar Diplomatic Relations from the Polish Central Archive of Historical Records in Warsaw (Archiwum Główne Akt Dawnych). The edition which is based on the facsimiles printed from the work of the Polish historian Dariusz Kołodziejczyk, takes the first edition of the documents from 1864 by Husain Faizkhanov account as well as the transcriptions made by Dariusz Kołodziejczyk from 2011 and by Refat Abdulcemilev in 2017.